Do stomata optimize turgor-driven growth? A new framework for integrating stomata response with whole-plant hydraulics and carbon balance - Potkay, Aaron (The New phytologist, 2023)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.